Tantalum nanoparticles reinforced polyetheretherketone coatings on titanium substrates: Bio-tribological and cell behaviour. (November 2022) - Cao, Lin; Yang, Junjie; Li, Jie; Zeng, Dahai; Lin, Zhidan; Yu, Zhentao; Hang, Suyuan; Li, Wei; Wang, Qiwei; Li, Shuangjian; Zhang, Peng
Abstract: As a biomaterial for bone repair, the application of polyetheretherketone (PEEK) has been limited by its poor wear resistance and cell behaviour. Inspired by the double 'soft-hard' phase structure, tantalum (Ta)/PEEK composite coating was fabricated on a titanium surface . All composite coatings had a lower friction coefficient and wear resistance under fetal bovine serum conditions. The adhesion, proliferation, and osteogenic differentiation of rat bone osteoblastic cells (MC3T3-E1) and mononuclear macrophage cells (RAW264.7) on the Ta/PEEK composite coating was enhanced. In particular, composite coatings effectively reduced inflammatory markers, with cytokines TGF-β and IL-10 released. As a result, titanium alloys with Ta reinforced PEEK coatings could exhibit improved bioactivity and tribology.